Synthesis and characterization of rhena[10]annulynes. Issue 12 (4th May 2022) - Cao, Qiang; Wang, Ping; Cai, Yuanting; Hua, Yuhui; Zheng, Shaohui; Cheng, Xu; He, Guomei; Wen, Ting-Bin; Chen, Jiangxi
Abstract : The first rhena[10]annulyne bearing a ten-membered metallacycle with a single metal center has been synthesized. The ring shows a deshielding effect that suggests a π-conjugation present in the metallacycle. Abstract : Most reported metallacycles are limited to small cyclic complexes that contain six-membered or smaller rings. Larger-membered metallacycles are still rare and mainly focus on dimetallacycles. Herein, we report the first rhena[10]annulyne, a ten-membered metallacycle with a single metal center. The complex was isolated by the treatment of a silyl alkyne tethered rhenium vinyl carbyne complex with tetrabutylammonium fluoride. Its structure was identified by single-crystal X-ray diffraction and NMR studies. DFT calculation studies suggest that there is a thermodynamic origin for the conversion of the rhenavinylcarbyne complex to a rhena[10]annulyne. The rhena[10]annulyne represents a new metallacycle bearing a large ten-membered ring.